Constitutional neutrality: an essay on the essential meaning of freedom of speech - Martins Neto, João dos Passos (Revista de Investigações Constitucionais, 2019)
The present essay explores the essential meaning of freedom of speech in the context of contemporary constitutional democracy. In addressing the question of how free speech constitutional clause should be understood in an universe full of controversial cases, the study articulates three main propositions: 1. Freedom of speech is the right not to be prevented from speaking or not to be punished for speaking based on the alleged unacceptability of an idea (taken as incorrect, inappropriate, stupid, irrelevant, shocking, dangerous, etc.); 2. Freedom of speech grants protection no matter the content of the message because the exchange of ideas is valuable for reasons other than the substantive qualities of what is said; to be worthy of protection, speech does not need to be infallible, clever or polite, but only play an expressive role in the process of discussion; 3. Freedom of speech doesn’t collide with rights of others, especially in the case of assertive speech acts, that is, assertions of facts and values that the speaker sincerely believes to be true or correct; even when the content sounds outrageous, asserting something doesn’t imply violation of anyone’s right, but rather it means the exercise of one’s own right.